Flavor for all : everyday recipes / creative pairings - Briscione, James, 1980-; Parkhurst, Brooke (Houghton Mifflin Harcourt, 2020)
"Simple, dynamic, flavor-packed recipes from the authors of The Flavor Matrix-informed by the science of flavor pairing but accessible enough for every cook"--